2011
DOI: 10.1248/cpb.59.388
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Herbal Alkaloids on the Tumor Necrosis Factor-.ALPHA. and Nitric Oxide Production in Lipopolysaccharide-Stimulated RAW264 Macrophages

Abstract: Uncontrolled production of proinflammatory cytokines is the primary cause of chronic inflammatory diseases such as rheumatoid arthritis, psoriasis, and ulcerative colitis. 1)Among the above cytokines, tumor necrosis factor-a (TNFa) plays important multiple roles in the pathobiology of inflammation, and induces itself as well as other inflammatory cytokines. Nitric oxide (NO) is another potent proinflammatory mediator. NO at low concentrations is the essential regulator of physiological homeostasis in cardiovas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 25 publications
0
35
0
Order By: Relevance
“…Sesquiterpenes have been also shown to have an anti-inflammatory potential by the inhibition of NO and TNF-a production (Jin et al 2006). Moreover, alkaloids have been shown to possess anti-inflammatory activity by inhibiting the action of arachidonic acid metabolism via the cycloxygenase and 5-lipoxygenase pathways (Barik et al 1992;Chao et al 2009) and by inhibiting TNF-a secretion (Yui et al 2001;Yamazaki & Kawano 2011). Based in these results, the in vitro and in vivo anti-inflammatory and analgesic activities of the crude extract and its polar fractions from the red algae L. obtusa could be also attributed to the presence of various other secondary metabolites especially terpenoids and alkaloids.…”
Section: Discussionmentioning
confidence: 99%
“…Sesquiterpenes have been also shown to have an anti-inflammatory potential by the inhibition of NO and TNF-a production (Jin et al 2006). Moreover, alkaloids have been shown to possess anti-inflammatory activity by inhibiting the action of arachidonic acid metabolism via the cycloxygenase and 5-lipoxygenase pathways (Barik et al 1992;Chao et al 2009) and by inhibiting TNF-a secretion (Yui et al 2001;Yamazaki & Kawano 2011). Based in these results, the in vitro and in vivo anti-inflammatory and analgesic activities of the crude extract and its polar fractions from the red algae L. obtusa could be also attributed to the presence of various other secondary metabolites especially terpenoids and alkaloids.…”
Section: Discussionmentioning
confidence: 99%
“…Harmine showed stronger TNF-alpha suppressive activities than reference polyphenol and butein in RAW264 cells. Harmine was also found to suppress interleukin-6 production in RAW264 cells [42] .…”
Section: Effect Of Harmine Against Inflamationmentioning
confidence: 93%
“…Recently, we found that the herbal alkaloid, harmine has potential as anti-inflammatory agents that can suppress TNF-α and NO production [10]. We also found using a customdesigned assay for circadian oscillation in vitro that harmine extends the circadian period [11].…”
Section: Introductionmentioning
confidence: 90%
“…We also found using a customdesigned assay for circadian oscillation in vitro that harmine extends the circadian period [11]. The Amaryllidaceae alkaloid, lycorine (3, 12-didehydro-9, 10-[methylenebis(oxy)]-galanthan-1α, 2β-diol) also suppressed TNF-α and NO production, indicating powerful anti-inflammatory activity [10]. Lycorine also has antiviral and antimalarial properties as well as the ability to inhibit protein synthesis and cell growth [12].…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation